The Effect of Precipitation Hardening on Micro structural Welded Joint of Aluminum Alloy (2024T3) (University of Thi-Qar Journal for Engineering Sciences, 2014)
The aim of this work is to study the possibility of joining the Aluminum alloy (2024T3) by the Manual Metal Arc Welding(MMAW) using the (E4043) electrode, and studying the microscopic structure in the joint area.A )V-Butt joint) were prepared before and after the heat treatment then thermally treated after welding (Solution treating and aging). It was clear that the molten zone (Fusion Zone) will be containing epitaxial growth, also it contains the phase (Al2Cu) what it called copper-rich phase, that was in case of not using heat treatment, but when using heat treatment before welding, the copper-rich phase will be less and the heat treatment after welding will result in distortion of that phase.